2015
DOI: 10.1007/s00404-015-3702-5
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated microRNAs involved in the progression of cervical neoplasm

Abstract: Our study demonstrated that miRNAs are aberrantly expressed in cervical cancer and cervical preneoplastic lesions. These miRNAs may be involved in the progression of cervical neoplasm as potential tumor suppressor genes or oncogenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 36 publications
0
42
0
2
Order By: Relevance
“…miRNAs bind to the 3'-untranslated region of target mRNA sequences and subsequently repress their translation and expression (4). In addition, miRNAs are closely correlated with the development and progression of cervical cancer (5,6). They serve important roles in regulating the proliferation, apoptosis, invasion and metastasis of cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs bind to the 3'-untranslated region of target mRNA sequences and subsequently repress their translation and expression (4). In addition, miRNAs are closely correlated with the development and progression of cervical cancer (5,6). They serve important roles in regulating the proliferation, apoptosis, invasion and metastasis of cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation and progression of cervical cancer is a multi-step process, involving multiple factors and the transformation of normal cervical epithelium into cervical intraepithelial neoplasia, which subsequently transforms into invasive cervical cancer (2,3). A number of studies have demonstrated that persistent infection with high-risk human papillomavirus (HPV) serves an important role in the initiation and progression of cervical cancer (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…12Y14 However, the role of miRNAs in cervical cancer development and precise mechanism of its actions remains largely elusive. Several recent microarray analyses showed that miR-195 expression was significantly lower in cervical cancer tissues relative to normal tissues, 15,16 and a large body of studies has found that miR-195 regulates tumor progression in a variety of cancers as a tumor-suppressive miRNA. 17Y19 However, the potential involvement of miR-195 in cervical cancer remains much to be determined.…”
mentioning
confidence: 98%